Lack of amanah (trust) and its Implication in governance: issues of corruption in Malaysia - Ali, Mohammed Farid (2019)
The study examines the concept of Amanah (Trust) as spinal-quality of leadership for administering the works of governance and what behavior the leaders could turn out to have if trust is violated. The study made its findings from the Malaysian corruption related court cases to warrant the important roles the Amanah (Trust) plays in keeping the integrity of the governance intact for the well-being of the state. This research found that unchecked power lures towards indiscriminate violation of trust, the study therefore proposes strict measures to control abuse and excessive power entrusted into the custody of the leader such as decentralization of authority and strengthening the power of the anticorruption institution.